J.M.G. Le Clézio and Baruch Spinoza: Understanding and Accepting the ‘God’ of Material Reality (ENTHYMEMA, 2013)
The Dutch philosopher Baruch Spinoza and the contemporary Franco-Mauritian author J.M.G. Le Clézio place great emphasis on the materiality of the human condition. For both of these extremely divergent thinkers, the path to existential redemption and spiritual edification is inseparable from the biotic network of life to which we are inextricably linked. Given that nothing exists in a cosmic vacuum in complete isolation from other material organisms, Spinoza and Le Clézio urge the modern subject to deconstruct seductive, anthropocentric ideology and to embrace reality. Indeed, understanding and accepting our own corporality in addition to exploring the complex relationship between ourselves and the cosmic forces that sustain us is perhaps the only true path to self-actualization that allows us to project meaning upon the absurdity of the universe.